Impact of Airline Service Quality and Safety Perception on Airline Brand Loyalty: Mediating Role of Passenger Expectation - Farooq, Suhail; Zulqurnain, Muhammad; Majid, Muhammad Bilal; Shafqat, Syed Zaeem (Pakistan Journal of Humanities and Social Sciences, 2023)
This research aims to examine the influence of airline service quality and safety perception on brand loyalty. Furthermore, passenger anticipation employed as mediating variable for in-depth research. In order to achieve the goal of this research, data were gathered from a sample of 384 customers who use airline services. The convenient sampling approach was employed for data collection. The findings from the structural equation modelling revealed that brand loyalty has a considerable impact on the evaluation of airline services quality and safety perception. Additionally, the study identified the important mediating function of passenger expectation. This research assists the authorities and managers in the airline sector in formulating effective and efficient strategies to meet customer demand and cultivate brand loyalty.